2022
DOI: 10.4103/mjdrdypu.mjdrdypu_406_20
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pelvic Proprioceptive Neuromuscular Facilitation on Trunk Stability and Gait Parameter in Stroke Patients

Abstract: Background and Purpose: Neurological deficits after stroke are impaired motor functions including balance and gait. Such gait deviations are associated with decreased gait velocity followed by a change in the timing and distance with each step cover. The pelvic proprioceptive neuromuscular facilitation (PNF) facilitates the trunk and lower extremity motion and also provides the stability of trunk. The aim of this review is to systematically evaluate the effectiveness of Pelvic PNF on gait and trunk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The treatment carried out in the home was walking, standing on one leg, climbing one stair up and down, and squatting [ 13 ]. For improving gait parameters and pelvic alignment, the pelvic PNF technique was used regularly for better outcomes, and in the study by Shah et al, it was shown to be effective and the same result was obtained in our study [ 14 ]. To normalize the tone, quick stretch, and heavy joint compression were used as facilitatory techniques and were proven effective in normalizing tone as the Patel et al study suggested.…”
Section: Discussionsupporting
confidence: 86%
“…The treatment carried out in the home was walking, standing on one leg, climbing one stair up and down, and squatting [ 13 ]. For improving gait parameters and pelvic alignment, the pelvic PNF technique was used regularly for better outcomes, and in the study by Shah et al, it was shown to be effective and the same result was obtained in our study [ 14 ]. To normalize the tone, quick stretch, and heavy joint compression were used as facilitatory techniques and were proven effective in normalizing tone as the Patel et al study suggested.…”
Section: Discussionsupporting
confidence: 86%